Relative Impacts of Projected Climate and Land Use Changes on Terrestrial Water Balance: A Case Study on Ganga River Basin - Saha, Anamitra; Ghosh, Subimal (Frontiers in Water, 2020)
The Ganga river basin, being one of the largest river basins in South-East Asia, with area over 1 million Km2 and population over 400 million, is highly vulnerable to water scarcity due to climate change and rapid growth in agriculture, industrialization and urbanization. To understand the potential impact of climate and land use changes on regional terrestrial water balance has become crucial for ensuring appropriate water management strategies for adaptation and mitigation purposes. In this study we employ an RCP-SSP (Representative Concentration Pathways - Shared Socioeconomic Pathways) scenario framework (1.5°C and 2°C warming scenarios and SSP1-5) to explore the relative impacts of projected 21st century climate and land use changes on the surface hydrology of the Ganga river basin. By statistically comparing the hydrological responses of each combination of socioeconomic and climate mitigation pathways against a control scenario, we distinguish between the impacts of each scenario. We also analyse our data in a conceptual framework to understand how climatic and land use factors impact the basin characteristics and which one among them is projected to be the dominant factor in our study region. Our results show that, in terms of hydrologic impact assessment, climate change mitigation pathways are the dominant factor and the land use changes associated with socio-economic pathways contribute little to the projected future changes.